E-Banking Service Quality and Customer Satisfaction with Moderator Factor - Trung Kim Quoc Nguyen (Emerging Science Journal)
This study explores the dimensions of e-banking service quality influencing customer satisfaction in commercial banks in Vietnam, with a focus on the moderating role of word of mouth (WOM). Using a mixed-methods approach, combining qualitative insights with quantitative analysis through Partial Least Squares Structural Equation Modeling (PLS-SEM), the study identifies five key dimensions: transaction speed, efficiency, reliability, responsiveness, and confidentiality. The findings reveal that these dimensions significantly impact customer satisfaction, with a statistical significance of 1%. Additionally, WOM is found to strengthen the positive relationship between e-banking service quality and customer satisfaction, highlighting its role as a critical moderator. By integrating service quality and customer behavior perspectives, the research provides insights into how WOM amplifies the effects of high-quality e-banking services.